Colonization, indigenization, and the differential evolution of English: Some ecological perspectives. Issue 1 (March 2015) - MUFWENE, SALIKOKO S.; SMITH, LARRY E.; SRIDHAR, S.N.
ABSRACT This paper provides an overview of research on the emergence of creoles and pidgins, how these are related to 'indigenized Englishes, ' and whether these evolutions have occurred in fundamentally different ways from other colonial English varieties such as North American and Australian Englishes. The findings of this research strongly suggest that, from an ecological perspective, similar processes of language contact are crucial to the development of not only creoles and pidgins and world Englishes, but to all languages. In this perspective, creoles and pidgins should not be disenfranchised as examples of 'abnormal' varieties, but instead recognized as instances of natural language evolution.